2005
DOI: 10.1111/j.1540-627x.2005.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Social Capital in Venture Creation: Key Dimensions and Research Implications*

Abstract: This study was built upon Nahapiet and Ghoshal's three dimensions of social capital-structural, relational, and cognitive. It addresses three research questions:(1) Are there significant differences in social capital between nascent entrepreneurs and the general public (control group)? (2) Are there significant differences in social capital between technology and nontechnology nascent entrepreneurs? (3) How do the three dimensions of social capital interact among themselves across different sample groups? Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
336
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(363 citation statements)
references
References 51 publications
17
336
1
9
Order By: Relevance
“…In fact, the early formation of a business, networking provides a bridging function to the environment and attenuates unfavourable environmental influences on business development, thus having a positive effect on survival (Davidsson and Honig, 2003;Kristiansen, 2002;Littunen, 2000). Last, the importance of networking to the new venture creation process is highlighted by several authors (Baron and Markman, 2003;De Carolis and Saparito, 2006;De Carolis et al, 2009;Korunka et al, 2010;Liao and Welsch, 2005).…”
Section: Business Networkmentioning
confidence: 99%
“…In fact, the early formation of a business, networking provides a bridging function to the environment and attenuates unfavourable environmental influences on business development, thus having a positive effect on survival (Davidsson and Honig, 2003;Kristiansen, 2002;Littunen, 2000). Last, the importance of networking to the new venture creation process is highlighted by several authors (Baron and Markman, 2003;De Carolis and Saparito, 2006;De Carolis et al, 2009;Korunka et al, 2010;Liao and Welsch, 2005).…”
Section: Business Networkmentioning
confidence: 99%
“…In addition to the aforementioned literature, the hypotheses in the present study are founded upon ETZIONI's (1987) and LIAO and WELSCH's (2005) investigations. ETZIONI (1987: 175) suggests that 'the extent to which entrepreneurship is legitimate, the demand for it is higher; the supply of entrepreneurship is higher; and more resources are allocated to the entrepreneurial function'.…”
Section: Influence Of Regional Social Legitimacy Of Entrepreneurship mentioning
confidence: 99%
“…Liao and Welsch (2005) described different aspects of social capital as serving different purposes. Structural capital is supposed to enhance a nascent entrepreneur's ability to enterprise.…”
Section: Discussionmentioning
confidence: 99%
“…Since the seminal work of Putnam (1994), scholars have attempted to identify and verify different dimensions of social capital in different social contexts. One such theoretical proposition that applies strictly to the entrepreneurial context was developed by Nahapiet and Ghoshal (1998) and later used by other scholars including Liao and Welsch (2005). Authors identified three dimensions of social capital: structural, relational and cognitive social capital.…”
Section: Introductionmentioning
confidence: 99%